Amorphous nano-structured coatings prepared from CVD-composites - V. F. Zinchenko; I. R. Magunov; O. V. Mozkova; O. V. Sviridova; T. Truglas (Хімія, фізика та технологія поверхні)
The main idea of the work is the development of a cheap and easy method for the manufacture of nanostructured systems based on the Chemical Vapor Deposition (CVD). Beginning with a new class of materials for interference optics in the infrared (IR) range of the spectrum, the evaporation of composites of systems germanium-metal chalcogenide (oxide), in particular, of the Ge-ZnS and Ge-Sb2Se3 systems was studied. They evaporate in vacuum congruently, and upon condensation on substrates form nano-structured thin-film coatings. In the first of these systems, the coating has an X-ray amorphous nature: the formation of a nano-dispersed composite in a Ge-ZnS film is confirmed by the absence of characteristic peaks of Ge and ZnS in X-ray diffraction patterns, but the formation of a characteristic halo takes place. At the same time, upon evaporation and condensation of a sample of the Ge-Sb2Se3 system, a glassy structure is formed; this is confirmed by high-resolution transmission electron microscopy (TEM), where no crystalline regions were found. The energy-dispersive X-ray (EDX) spectroscopy measurements of the coating (about 10 at.% of Ge, 40 at.% of Sb and Se, respectively) indicate a certain deviation from the stoichiometry compared to the initial sample of the system. This may indicate a slightly lower volatility of germanium selenides compared to antimony selenides. The EDX line scans along the cross-section of the coating exhibited strong fluctuations in the concentration of elements, and, consequently, the heterogeneity of the coating in terms of composition. Both coatings have high mechanical strength (group 0). At the same time, their optical properties differ significantly: the refractive indices are 3.00 and 3.66 for the Ge-ZnS and Ge-Sb2Se3 systems, respectively. It is believed that nano-structuring in the above systems is due to the high capability of germanium to amorphize upon condensation on a glass substrate.